Strengthening of RC beam externallly using bamboo fibre reinforced composite : a study on Gigantochloa Scortechinii - Lee, Mei Chin (2018)
The use of fibre reinforced polymer as external strengthening in reinforced concrete (RC) structures which in need to carry out rehabilitation works. A study on Gigantochloa Scortechnii (Buluh Semantan) has been conducted to investigate the mechanical properties of the bamboo and its fibres to be used in composite fabrication. In this research, the bamboos are obtained from Raub, Pahang. In terms of mechanical properties of bamboo, tensile and compression test between the raw and oven-dried bamboo specimens have been performed. On the other hand, for the composite plate fabrication, the bamboo fibres had been treated with 10 % of sodium hydroxide (NaOH) for 48 hours. The bamboo fibres with a density of 0.75 g/cm3 are mixed with epoxy resin matrix in the ratio of 2:3. Tensile and flexural strength tests are executed to compare the characteristics between the neat epoxy and bamboo fibre-epoxy composite plate (BFECP). Moreover, the BFECP is bonded to the reinforced concrete (RC) beam as external strengthening material. Four-points loading test is performed to study the structural behaviour between the control (CB), un-strengthened (USTB) and strengthened beam (SSTB). From the results, the tensile and compressive strength of the oven-dried bamboo specimens are higher than in raw condition, which is 48.77 % and 31.68 %, respectively. Meanwhile, the BFECP are 309.73 % and 820.11 %, respectively, greater than neat epoxy in terms of tensile and flexural strength. On the other hand, the ultimate load sustained by the strengthened beam is 16.81 % and 23.84 % higher than control beam and un-strengthened beam, respectively. In terms of crack propagation, the flexural cracks were found in the mid-span of beam specimens while only control beams failed in bending and experienced diagonal tension failure. This signifies that bamboo fibres-epoxy composite plate has potential to be used as an alternative strengthening material for synthetic reinforced polymer.